Kaizen Cultural Analysis (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) Against Employee Performance at PT. Smelting - Amin Maaruf (International Consortium of Education and Culture Research Studies, 2021)
This study aims to analyze the extent of the influence of kaizen culture on the performance of employees of PT. Smelting. The population in this study were employees of PT Smelting. The sampling method uses probability sampling, namely by simple random sampling technique. Samples taken were 60 respondents. While the analysis used is Multiple Linear Regression. Based on the results of the research and discussion of the results of the study, it has been concluded and it can be concluded that the kaizen culture has a positive effect on the performance of employees of PT. Smelting either partially or simultaneously with the most dominant variable is seiketsu.